A two-year comparative assessment of retention of arch width increases between modified vacuum-formed and Hawley retainers: a multi-center randomized clinical trial - Asma Ashari; Nik Mukhriz Nik Mustapha; Jonathan Jun Xian Yuen; Zhi Kuan Saw; May Nak Lau; Lew Xian; Alizae Marny Fadzlin Syed Mohamed; Rohaya Megat Abdul Wahab; Chiew Kit Yeoh; Malathi Deva Tata; Sindhu Sinnasamy (Progress in Orthodontics, 2022)
Abstract Objectives To compare the clinical effectiveness of Hawley retainers (HRs) and modified vacuum-formed retainers (mVFRs) with palatal coverage in maintaining transverse expansion throughout a 24-month retention period and to assess the subjects’ perception toward the retainers. Materials and methods The trial accomplished blinding only by the outcome assessor and data analyst. Data were collected from post-orthodontic treatment patients who met the inclusion criteria. Thirty-five subjects were randomly allocated using a centralized randomization technique into either mVFR (n = 18) or HR group (n = 17). Dental casts of subjects were evaluated at debond (T0), 3-month (T1), 6-month (T2), 12-month (T3), and 24-month retention (T4). The intercanine width (ICW), interpremolar width (IPMW), interfirst molar mesiobuccal cusp width (IFMW1), and interfirst molar distobuccal cusp width (IFMW2) were compared between groups over time using Mixed ANOVA. A pilot-tested and validated questionnaire consisting of six items were given at T4. Subjects were instructed to rate their retainer in terms of fitting, speech, appearance, oral hygiene, durability, and comfort on a 100-mm Visual Analogue Scale (VAS). Results No statistically significant differences in arch width were found between the two groups at ICW (P = .83), IPMW (P = 0.63), IFMW1 (P = .22), and IFMW2 (P = .46) during the 24-month retention period. Also, no statistically significant differences were found between perception of both retainers in terms of fitting, speech, oral hygiene, durability, and comfort (P > .05) after 24-month wear. The appearance of mVFRs was rated significantly higher compared to HRs (P < .05). Conclusions HR and mVFR have similar clinical effectiveness for retention of transverse expansion cases in a 24-month retention period. Both retainers were perceived to be equal in terms of fitting, speech, oral hygiene, durability, and comfort. Subjects in the mVFRs group found their retainers to be significantly more esthetic than those in HRs group.